A study on identifying and analyzing problem of container movement at Keretapi Tanah Melayu Berhad / Wan Shaharir Johan Haris - Johan Haris, Wan Shaharir (1995)
As an introduction for the thesis in Chapter One, it is appropriate to look at the basic foundation of the research. Mainly the researcher had list down all the introduction aspect of the thesis which is the objective of the study, problem statement, benefit of the study and by the end of the day he should be able to answer the research question which had been mentioned in this chapter. To give a clear picture and a better understanding on the research topic; the essential literature review had been included in this chapter. Through literature review all the relevant information regarding the research will be presented base on the reading material by various authors.